Rancang Bangun Sistem Manajemen Jaringan dan Suhu untuk Data Center menggunakan Raspberry Pi dan Zabbix - Musakkarul Mu’minim Lambacing; Ririn Apriliani; Dolly Virgian Shaka Yudha Sakti (Ikatan Ahli Informatika Indonesia, 2020)
Companies engaged in telecommunications usually have main services as Internet Service Providers. Its customers are spread outside the island. To maintain and monitor the availability of its services, a centralized monitoring system is needed that can be used to monitor in real time. In this study a system was designed to monitor the overall work of the device and also monitor the temperature where the device is located. To save the cost of making this system, the device uses Raspberry Pi which is quite cheap. An administrator can monitor devices that exist in the data center via the online system. When there is a device failure, the system will immediately report this to the administrator via email.